Lysosome Interference Enabled by Proton‐Driven Dynamic Assembly of DNA Nanoframeworks inside Cells. (27th July 2022) - Dong, Yuhang; Li, Feng; Lv, Zhaoyue; Li, Shuai; Yuan, Meihe; Song, Nachuan; Liu, Jinqiao; Yang, Dayong
Abstract: Coupling materials chemistry systems to biological processes is a promising way to rationally modulate lysosomal functions. A proton‐driven dynamic assembly of a DNA nanoframework inside cells coupled with the lysosome‐mediated endocytosis pathways/lysosomal maturation, gives the rational modulation of lysosomal functions, which we term "lysosome interference". Through lysosome‐mediated endocytosis, the DNA nanoframework with acid‐responsive semi‐i‐motif enters the lysosome and assembles into an aggregate in a process triggered by lysosomal acidity. The aggregate is suitable for long‐term retention. The consumption of protons resulted in lysosomal acidity reduction and hydrolase activity attenuation, thus hindering the degradation of nucleic acid drugs in the lysosome and improving gene silencing effects. This study shows a new way to achieve lysosome interference by coupling the subcellular microenvironment with a precisely programmable assembly system. Abstract : Proton‐driven dynamic assembly of DNA nanoframeworks inside cells couples with the lysosome‐mediated endocytosis pathways/lysosomal maturation to give the rational modulation of lysosomal functions. These include lysosomal acidity reduction and hydrolase activity attenuation, thereby improving the delivery efficiency of nucleic acid drugs.